DEVELOPMENT OF WEB-BASED LEARNING MEDIA AT SMA NEGERI 1 BESITANG - Andi Akbar Suparto; Albadi Sinulingga; Sanusi Hasibuan (Universitas Negeri Medan, 2021)
The purpose of this study was to produce a product in the form of web-based learning media for physical education subjects for class X drugs at SMA Negeri 1 Besitang. The research method used in this study is a research and development method consisting of 9 stages, namely: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product trials, (7) product revisions, (8) usage trials and (9) product revisions. The pilot sample in this research and development was teachers and students of class X at SMA Negeri 1 Besitang. The trial sample in small groups in this study amounted to 26 people. The trial sample in the large group in this study amounted to 42 people. Collecting data using questionnaires, interview guidelines, and observation sheets. The data analysis technique was carried out by calculating the percentage of answers to each statement item given to respondents, namely material experts, media experts, learning experts, teachers and students. This study resulted in the assessment data of small group student responses having an average percentage value of 84.4% being in the